Semen impairment and occurrence of SARS-CoV-2 virus in semen after recovery from COVID-19. Issue 6 (1st March 2021) - Gacci, M; Coppi, M; Baldi, E; Sebastianelli, A; Zaccaro, C; Morselli, S; Pecoraro, A; Manera, A; Nicoletti, R; Liaci, A; Bisegna, C; Gemma, L; et al.
Abstract: STUDY QUESTION: How is the semen quality of sexually active men following recovery from severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection? SUMMARY ANSWER: Twenty-five percent of the men with recent SARS-Cov-2 infections and proven healing were oligo-crypto-azoospermic, despite the absence of virus RNA in semen. WHAT IS KNOWN ALREADY: The presence of SARS-CoV-2 in human semen and its role in virus contagion and semen quality after recovery from coronavirus disease 2019 (COVID-19) is still unclear. So far, studies evaluating semen quality and the occurrence of SARS-CoV-2 in semen of infected or proven recovered men are scarce and included a limited number of participants. STUDY DESIGN, SIZE, DURATION: A prospective cross-sectional study on 43 sexually active men who were known to have recovered from SARS-CoV2 was performed. Four biological fluid samples, namely saliva, pre-ejaculation urine, semen, and post-ejaculation urine, were tested for the SARS-CoV-2 genome. Female partners were retested if any specimen was found to be SARS-CoV-2 positive. Routine semen analysis and quantification of semen leukocytes and interleukin-8 (IL-8) levels were performed. PARTICIPANTS/MATERIALS, SETTING, METHODS: Questionnaires including International Index of Erectile Function and Male Sexual Health Questionnaire Short Form were administered to all subjects. The occurrence of virus RNA was evaluated in all the biological fluids collected by RT-PCR. Semen parameters were evaluated according to the World Health Organization manual edition V. Semen IL-8 levels were evaluated by a two-step ELISA method. MAIN RESULTS AND THE ROLE OF CHANCE: After recovery from COVID-19, 25% of the men studied were oligo-crypto-azoospermic. Of the 11 men with semen impairment, 8 were azoospermic and 3 were oligospermic. A total of 33 patients (76.7%) showed pathological levels of IL-8 in semen. Oligo-crypto-azoospermia was significantly related to COVID-19 severity ( P  < 0.001). Three patients (7%) tested positive for at least one sample (one saliva; one pre-ejaculation urine; one semen and one post-ejaculation urine), so the next day new nasopharyngeal swabs were collected. The results from these three patients and their partners were all negative for SARS-CoV-2. LIMITATIONS, REASONS FOR CAUTION: Although crypto-azoospermia was found in a high percentage of men who had recovered from COVID-19, clearly exceeding the percentage found in the general population, the previous semen quality of these men was unknown nor is it known whether a recovery of testicular function was occurring. The low number of enrolled patients may limit the statistical power of study. WIDER IMPLICATIONS OF THE FINDINGS: SARS-CoV-2 can be detected in saliva, urine, and semen in a small percentage of men who recovered from COVID-19. One-quarter of men who recovered from COVID-19 demonstrated oligo-crypto-azoospermia indicating that an assessment of semen quality should be recommended for men of reproductive age who are affected by COVID-19. STUDY FUNDING/COMPETING INTEREST(S): None. TRIAL REGISTRATION NUMBER: N/A.